Fostering Children's Independence and Confidence Through Traditional Jajangkungan Games in The Kober Karima Environment - Nurhasanah; Selamet; Saepul Millah (International Journal on Education Issues, 2025)
Purpose – This study aims to explore the role of traditional games, specifically Jajangkungan, in fostering independence and self-confidence among early childhood learners amid the decline of traditional play due to modernization and digital dominance. Design/Methodology/Approach – Employing a qualitative descriptive method with a case study design, this research was conducted at Kober Karima Early Childhood Center. Data were collected through semi-structured interviews with children, parents, and educators, supported by participatory observation and documentation. The data were analyzed using Miles and Huberman’s model of data reduction, presentation, and conclusion drawing. Findings – The findings reveal that Jajangkungan serves as an effective educational medium that integrates physical, psychological, and social development. Physically, it enhances motor coordination, balance, and body control. Psychosocially, the repetitive process of falling, standing, and mastering the game cultivates perseverance, independence, and confidence. Both educators and parents acknowledge its pedagogical value: teachers view it as a character-building tool, while parents regard it as a complementary means of holistic development. Originality/Value – The originality of this study lies in highlighting Jajangkungan as a culturally grounded learning model that harmonizes traditional values with modern educational objectives. By reviving traditional play as an alternative medium for early childhood education, this research offers a sustainable approach to character education that balances physical vitality, emotional resilience, and social awareness in the digital era.